CYTOCHROME P450 CYP1B1*2 GENE AND ITS ASSOCIATION WITH T2D IN TABUK POPULATION, NORTHWESTERN REGION OF SAUDI ARABIA - Elfaki, Imadeldin; Almutairi, Fahad M; Mir, Rashid; Khan, Roaid; Abu-duhier, Faisel (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Cytochrome P450 1B1 (CYP1B1) is involved in the activation of procarcinogens and steroid metabolism. Genetic variants of CYP1B1are associated with altered catalytic activity and disease phenotypes. The purpose of this study was to investigate the role of CYP1B1 (rs1056827) polymorphism in inducing T2D. Methods: This cross-sectional study enrolled 113 subjects of T2D and 120 controls. DNA was isolated from blood. Genotyping of the rs1056827 wasdone by allele-specific polymerase chain reaction. The frequency of alleles and genotype distribution was compared in T2D cases and healthy controls.Statistical analysis was performed with SPSS, Chi-square, and Fisher exact test. Hardy-Weinberg equilibrium was tested by a χ2 test. The associations between rs1056827 variant genotypes and T2D were estimated by computing the odds ratios and their 95% confidence intervals (CI) from univariate and multivariate logistic regression analysis. Results: A significant association of rs1056827 was found between T2D cases and controls (p<0.0001). When GG genotype was compared with GT genotype a significant association was found with odd ration (OD)0.24 (95% CI: (0.131–0.452) and risk ratio (RR) 0.45 (0.30–0.67) times the risk of T2D heterozygous with the G/T allele (p≤0.0002). In a comparison of GG homozygous with the TT homozygous, there was no significant association with the OD 0.38 (95% CI: (0.02–6.51) RR 0.55(0.13–2.35), p<0.49. When G allele was compared with the T allele a highly significant association with OD 0.54 (95% [CI]: (0.37–0.80) RR 0.75(0.630–0.897) < p≤0.003 suggesting a possible dominant effect of this polymorphism on T2D risk. Conclusion: This result suggests a significant association between rs1056827G>T polymorphism and T2D. This finding is limited due to the smaller sample size and can be validated by large sample size studies.